APPLICATION OF AUDIO VISUAL LEARNING TO IMPROVE PAI LEARNING OUTCOMES ON THE MATERIAL OF ASMAUL HUSNA CLASS IV SDN 056594 MENJAHONG KUALA DISTRICT, LANGKAT REGENCY - Agustaria (Journal of Quality Islamic Education Research, 2025)
application of audio-visual media in Islamic Religious Education subject matter makes it easier for teachers to achieve learning objectives, namely in improving the learning outcomes of grade IV students. This can be seen from the percentage of classical learning completion at each stage which has increased, in cycle I it was 42%, and in cycle II the learning completion of students reached 92%. The average class value also increased significantly, namely in cycle I it was 67, and in cycle II it increased to 87. This means that the target set by the researcher has been achieved with the previously determined indicators, namely the percentage of classical completion reaching 85% and the Minimum Completion Criteria (KKM) per individual of 70.